Exploring the Effects of Teacher Education on Teacher Quality and Student Achievement in Pakistan - Mahrukh Zahid; Mehvish Saleem (International Journal of Experiential Learning & Case Studies)
Amongst a variety of resources present, a teacher is considered to be the primary tool for enhancing the process of student learning. To be able to act as effective “agents of change” for their student, the teacher needs to enhance personal and pedagogical skills which can primarily be achieved through teacher education. This paper aims to be contributing to a broader understanding of language teacher education in the context of Pakistan. Employing a case study research method, the present study explored the ways in which teachers’ pre-service education affects teacher quality and student learning. A total of two tertiary-level novice teachers and seven first year undergraduate students from a public sector university in Pakistan participated in this study. Data were generated using teacher observation, teacher and student interviews, document analysis including teacher lesson plans and diary, course outlines and students’ work samples. Thematic analysis of the data showed contradictory results between the classroom practices of the teachers and their effect on students’ learning. The teacher with pre-service education used appropriate methodology and made well informed decisions which resulted in improvement of students’ learning. In contrast, the other teacher used traditional modes of teaching. Though happy with the classes, students found no practical use of what they learnt in the lessons. The study concludes that pre-service teacher education should to be made compulsory for individuals who wish to become teachers.